Geophysical interpretation of tectonic features in Bangladesh (Journal of Nepal Geological Society, 1998)
Bangladesh occupies the major part of the Bengal basin. It is mainly a plain fluvi-dieltaic land. Except the eastern and northeastern Tertiary hilly region, the whole country is covered with thick Quaternary sediments.Tectonic features in Bangladesh, except the eastern and northeastern hilly structures, are hidden under thick cover of sediments. Gravity anomalies dearly show the locations of major subsurface tectonic features of the country, namely a) Himalayan foredeep, b) Rangpur platform, c) Hinge zone, d) Surma basin and e) Bengal foredeep. Magnetic anomalies and the seismic sections also support the gravity results.Shape, extent and depth of the tectonic features in Bangladesh are interpreted from geophysical data, particularly from the gravity data supported by available geological and drilling information. Interpretation shows that the Rangpur platform, situated in the northwestern Bangladesh, is the shallowest subsurface tectonic feature in the country. The northern part of the Rangpur platform slopes down to the Himalayan foredeep and the southern part to the Hinge zone. The Surma Basin, containing very thick sediments, lies in north-east corner of the country; and the Bengal foredeep, the most extended tectonic feature, occupies the southern deltaic part of the country. The Fold Belt, the only exposed tectonic feature, lies in the eastern and northeastern hilly region of the country.